Debate - Trafficking as a Floating Signifier: The view from Brazil - Davida, Grupo (Anti-Trafficking Review, 2015)
The fact that the United Nations (UN) Trafficking Protocol is not an autochthonous product of the Brazilian political system has resulted in its being brought into that system as a ‘floating signifier’: something that does not point to any actual object or agreed upon meaning.[1] People who wish to criminalise prostitution have attempted to bend the Protocol in that direction while prostitutes’ rights groups have used it to critique current Brazilian laws, emphasising the need to distinguish migration for voluntary, consensual sex work from trafficking. Groups concerned with organ trafficking (a crime for which there are practically no proven cases in Brazil) have managed to push their banner to the fore in the trafficking debate. Meanwhile, Brazil’s long-established and relatively successful anti-slave labour movement has been loath to ‘change their brand’, having already gained a considerable degree of institutionalisation prior to Brazil’s ratification of the Protocol in 2004. [1] C Lévi-Strauss, ‘Introduction à l'oeuvre de Marcel Mauss’ in Mauss, Sociologie et Anthropologie, Paris, 1950.